Cell Therapy in Joint Disorders. (January 2015) - Counsel, Peter D.; Bates, Daniel; Boyd, Richard; Connell, David A.
Context: Articular cartilage possesses poor natural healing mechanisms, and a variety of non-cell-based and cell-based treatments aim to promote regeneration of hyaline cartilage. Data Sources: A review of the literature to December 2013 using PubMed with search criteria including the keywords stem cell, cell therapy, cell transplantation, cartilage, chondral, and chondrogenic . Study Selection: Forty-five articles were identified that employed local mesenchymal stem cell (MSC) therapy for joint disorders in humans. Nine comparative studies were identified, consisting of 3 randomized trials, 5 cohort studies, and 1 case-control study. Study Type: Clinical review. Level of Evidence: Level 4. Data Extraction: Studies were assessed for stem cell source, method of implantation, comparison groups, and concurrent surgical techniques. Results: Two studies comparing MSC treatment to autologous chondrocyte implantation found similar efficacy. Three studies reported clinical benefits with intra-articular MSC injection over non-MSC controls for cases undergoing debridement with or without marrow stimulation, although a randomized study found no significant clinical difference at 2-year follow-up but reported better 18-month magnetic resonance imaging and histologic scores in the MSC group. No human studies have compared intra-articular MSC therapy to non-MSC techniques for osteoarthritis in the absence of surgery. Conclusion: Mesenchymal stem cell–based therapies appear safe and effective for joint disorders in large animal preclinical models. Evidence for use in humans, particularly, comparison with more established treatments such as autologous chondrocyte implantation and microfracture, is limited.